A numerical method for modeling ultrasonic guided waves in thin-walled waveguides coupled to fluids. (February 2019) - Mazzotti, M.; Miniaci, M.; Bartoli, I.
Highlights: Thin-walled waveguides in contact with fluids support complex guided wave modes. Coupling FEM and BEM at mid-surfaces simplifies meshing procedure. Fluid-loading can lead to non-dispersive L modes over broad frequency ranges. Mode coupling effects can determine spikes of attenuation values. Abstract: The paper presents a hybrid numerical method for the computation of the dispersion characteristics of ultrasonic guided waves propagating in isotropic and viscoelastic thin-walled waveguides in contact with fluids along their inner or outer wall. To this end, the solid waveguide is modeled by means of a Semi-Analytical Finite Element method implementing the first order shear deformation theory, while the effects of the fluid are taken into account by means of a regularized 2.5D Boundary Element Method with Helmholtz-type kernels. By coupling the two methods along the mid-surface of the solid waveguide, the dispersion relations of the elastic-acoustic system are obtained as the solution of a nonlinear eigenvalue problem in the complex axial wavenumbers for any fixed circular frequency. Two different case studies are presented: an oil-filled pipe and a water-loaded steel rectangular waveguide.